FENOMENOLOGI MEDIA VISUAL LAKON "MEREKA YANG MENUNGGU DI BANDA NAIRA" SUTRADARA WAWAN SOFWAN - Saing, Muhammad Erwan; Parmin, Parmin; Fitra, Hawwin (Boting Langi: Jurnal Seni Pertunjukan, 2025)
As the title implies, this study explores the phenomenology of visual media in a play by Wawan Sofwan, which is presented by cultivating historical memories of the exile of Indonesian national figures in an effort to preserve theater in Indonesia. This study uses a qualitative approach specific to the phenomenological paradigm. The research object is the play “Mereka Yang Menunggu di Banda Naira,” produced by the Titimangsa Foundation in 2021. Based on the assumption that visual media is the most popular form of media among theater audiences in Indonesia, this study examines public interest in historical memory and the aesthetics of theatrical performances through digital media. Data was collected through observation, interviews, and analysis of digital media. The results of the study indicate that visual media can expand audience access, strengthen the educational and aesthetic aspects of plays, and open new discourse in the documentation of modern theater, thereby helping the public and theater practitioners to package performances more effectively and avoid falling behind.